Measuring the Success of Grandpa Aki’s Short Video Series in Cross-cultural Transmission of Traditional Chinese Culture - Xu, Yeqing (European Scientific Journal, ESJ, 2024)
With the development of digitization and online platforms, short videos have become one of the ways to spread traditional Chinese culture. The success of Grandpa Aki’s short videos is a model of cross-cultural transmission of traditional Chinese culture, especially craftsmanship, via short videos. However, few scholars have talked about the implications of cross-cultural transmission of Chinese excellent traditional culture brought by Grandpa Aki’s short video series. The paper collected the title of the video, the view of the video and the proportion of positive comments and negative comments from the top 5 popular videos by using Python. The paper aims to identify (1) the characteristics of Grandpa Aki’s short video series; (2) the reasons for the success of Grandpa Aki’s short video series; (3) the implication of cross-cultural transmission of traditional Chinese culture from the success of Grandpa Aki’s short video series. The results show that 1) these videos are characterized by an immersive experience and spread traditional Chinese culture in detail. 2) The reasons for the success of these videos are the strong curiosity about traditional Chinese culture from overseas citizens, the value of traditional Chinese culture, the entertainment value of these videos and the resonance from people. The paper provides a thinking mode for scholars to solve the dilemma of overseas dissemination of traditional Chinese culture.